Evaluation of mango varieties for pulp processing suitability (Indian Journal of Arid Horticulture, 2021)
Thirty mango varieties were evaluated for pulp processing suitability. Fruit weight of mango varieties ranged from 122.67 to 583.34 g (CV = 10.02%), measured maximum for Sonia Malda (583.34 g) followed by Malda (572.34 g) and minimum fruit weight was noticed in Gourjeet (122.67 g). Pulp percentage varied from 53.96 to 75.28%, observed maximum in Sonia Malda (75.28%) followed by Malda (74.11%) and minimum pulp content was recorded in Gourjeet (52.85%) trailed by Cylone (53.96%). Sonia Malda (75.28%), Malda (74.11%), Mallika (72.00%) and Hybrid 18-8 (72.47%) were possessed more than 70% pulp content while 7 varieties (Amin Tehsilwala, Benzeer, Bombay Bottle, Creeping, Kharuspatti, Amrapali and Nisar Pasand) had pulp percentage between 65–70%. The stone percentage was considerably differed in mango genotypes (CV = 10.03%) and varied from 10.97 to 21.71%; maximum in Mithua and minimum in Mallika. Similarly, peel percentage ranged from 11.32 to 19.56%, minimum was observed in Sonia Malda (11.32%) followed by Malda (11.76%), Bombay Bottle (11.90%) and Amin Tehsilwala (11.77%) and maximum peel per cent was reported in Gourjeet (19.56%), Santra (19.23%) and Himsagar (18.73%). The varieties having high pulp content also showed high pulp/stone ratio and pulp/peel ratio. The highest pulp/stone ratio was noticed in Mallika (6.56), Malda (6.18) and Sonia Malda (5.37) and lowest was found in Gourjeet (2.09). Pulp TSS of most of the varieties was recorded between 15–20°Brix which was in line with the mango pulp industry standards (16°Brix). Maximum pulp TSS was observed in Amrapali (20.83°Brix) followed by Bombay Bottle (20.80°Brix), Mallika and Nisar Pasand (20.50°Brix) and Dashehari (20.13°Brix) while minimum TSS was noticed in Shere-a-Hayat (12.90°Brix) followed by Kalapahar (13.96°Brix). Based on pulp quantity it may be concluded that; Malda, Sonia Malda, Mallika, Hybrid 18-8, Amin Tehsilwala, Benzeer, Creeping, Kharuspatti, Amrapali, Dashehari, Nisar Pasand and Bombay Bottle were found suitable for pulp processing.